Testing the snake-detection hypothesis: larger early posterior negativity in humans to pictures of snakes than to pictures of other reptiles, spiders and slugs - Van Strien, Jan W.; Franken, Ingmar H. A.; Huijding, Jorg (Frontiers in Human Neuroscience, 2014)
According to the snake detection hypothesis (Isbell, 2006), fear specifically of snakes may have pushed evolutionary changes in the primate visual system allowing pre-attentional visual detection of fearful stimuli. A previous study demonstrated that snake pictures, when compared to spiders or bird pictures, draw more early attention as reflected by larger early posterior negativity (EPN). Here we report two studies that further tested the snake detection hypothesis. In Study, 1 we tested whether the enlarged EPN is specific for snakes or also generalizes to other reptiles. Twenty-four healthy, non-phobic women watched the random rapid serial presentation of snake, crocodile, and turtle pictures. The EPN was scored as the mean activity at occipital electrodes (PO3, O1, Oz, PO4, O2) in the 225–300 ms time window after picture onset. The EPN was significantly larger for snake pictures than for pictures of the other reptiles. In study 2, we tested whether disgust plays a role in the modulation of the EPN and whether preferential processing of snakes also can be found in men. Twelve men and twelve women watched snake, spider, and slug pictures. Both men and women exhibited the largest EPN amplitudes to snake pictures, intermediate amplitudes to spider pictures and the smallest amplitudes to slug pictures. Disgust ratings were not associated with EPN amplitudes. The results replicate previous findings and suggest that ancestral priorities modulate the early capture of visual attention.